Dangerous drugs, dangerous mothers: Gender, responsibility and the problematisation of parental substance use. (August 2019) - Flacks, Simon
If, as many would have it, the 'drugs problem' is among the more perilous and uncompromising challenges of our times, parental substance misuse represents one of its most insidious expressions. The past 15 years has seen the 'hidden harms' experienced by the children of drug users emerge as a principal concern for national policy actors and local service provision. However, there has been relatively little critique of the assumptions and epistemological foundations underscoring this policy shift, or of the preoccupation with the 'family' in drug policy in general. Through examination of seminal policy documents relating to parental substance misuse, and using Carol Bacchi's 'What's the Problem Represented to Be?' (WPR) approach, this article attends more closely to the formulation of parental drug use as a significant policy problem, and to the family as a principal site for the constitution of drug harms.